Cost-effectiveness of modified-release prednisone in the treatment of moderate to severe rheumatoid arthritis with morning stiffness based on directly elicited public preference values - Dunlop W; Iqbal I; Khan I; Ouwens M; Heron L (Dove Medical Press, 2013)
William Dunlop,1 Itrat Iqbal,1 Ifty Khan,2 Mario Ouwens,3 Louise Heron4 1Mundipharma International Limited, Cambridge, 2University College London, London, United Kingdom; 3Mapi HEOR, Houten, The Netherlands; 4Adelphi Values, Macclesfield, Cheshire, United Kingdom Background: Assessing the cost-effectiveness of treatments in rheumatoid arthritis (RA) is of growing importance due to the chronic nature of the disease, rising treatment costs, and budget-constrained health care systems. This analysis assesses the cost-effectiveness of modified-release (MR) prednisone compared with immediate-release (IR) prednisone for the treatment of morning stiffness due to RA. Methods: A health state transition model was used to categorize RA patients into four health states, defined by duration of morning stiffness. The model applied a 1-year time horizon and adopted a UK National Health Service (NHS) perspective. Health benefits were measured in quality-adjusted life years (QALYs) and the final output was the incremental cost-effectiveness ratio (ICER). Efficacy data were derived from the CAPRA-1 (Circadian Administration of Prednisone in Rheumatoid Arthritis) study, drug costs from the British National Formulary (BNF), and utility data from a direct elicitation time-trade-off (TTO) study in the general population. Sensitivity analyses were conducted. Results: Mean treatment costs per patient were higher for MR-prednisone (£649.70) than for IR-prednisone (£46.54) for the duration of the model. However, the model generated an incremental QALY of 0.044 in favor of MR-prednisone which resulted in an ICER of £13,577. Deterministic sensitivity analyses did not lead to significant changes in the ICER. Probabilistic sensitivity analysis reported that MR-prednisone had an 84% probability of being cost-effective at a willingness-to-pay threshold of £30,000 per QALY. The model only considers drug costs and there was a lack of comparative long-term data for IR-prednisone. Furthermore, utility benefits were not captured in the clinical setting. Conclusion: This analysis demonstrates that, based on the CAPRA-1 trial and directly elicited public preference values, MR-prednisone is a cost-effective treatment option when compared with IR-prednisone for RA patients with morning stiffness over one year, according to commonly applied UK thresholds (£20,000–£30,000 per QALY). Further research into the costs of morning stiffness in RA is required. Keywords: modified-release prednisone, rheumatoid arthritis, morning stiffness, cost-effectiveness analysis, cost utility analysis, quality of life